2017
DOI: 10.3171/2016.5.spine1621
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging–based measures predictive of short-term surgical outcome in patients with Chiari malformation Type I: a pilot study

Abstract: OBJECTIVE This study identifies quantitative imaging-based measures in patients with Chiari malformation Type I (CM-I) that are associated with positive outcomes after suboccipital decompression with duraplasty. METHODS Fifteen patients in whom CM-I was newly diagnosed underwent MRI preoperatively and 3 months postoperatively. More than 20 previously described morphological and physiological parameters w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…24 Some, including us, believe that reducing the size of the cerebellar tonsils contributes to the enlargement of the cisterna magna and initiates ascent of the tonsils. 13 Duraplasty may affect intracranial compliance 5 and appears to be associated with a lower risk of reoperation. 54…”
Section: Surgery and Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Some, including us, believe that reducing the size of the cerebellar tonsils contributes to the enlargement of the cisterna magna and initiates ascent of the tonsils. 13 Duraplasty may affect intracranial compliance 5 and appears to be associated with a lower risk of reoperation. 54…”
Section: Surgery and Indicationsmentioning
confidence: 99%
“…Intracranial compliance and pressure relationships offer an important area of study. 5 Further study of fluid hydrodynamics and pulsatility may also add to our understanding of both the Chiari anomaly and syringomyelia. The relationship of Chiari anomaly to HCTDs and craniocervical instability is in need of clarification, and there would be advantages to a clearer definition of the genetic bases of Chiari anomalies.…”
Section: Future Directionsmentioning
confidence: 99%
“…They found that ∼80% of the patients experienced relief from the symptoms and signs of CMI, whereas the remaining 20% showed no improvement after surgery. [7] In some studies, the percentage of unfavorable outcomes after PFD was as high as 30%, [8] although a subsequent report noted that postoperative magnetic resonance imaging (MRI) reflected adequate decompression in two-thirds of the patients with unfavorable outcomes. [9] The high rate of unfavorable outcomes has been attributed to poor patient selection rather than to the surgical procedure.…”
Section: Introductionmentioning
confidence: 99%
“…[9] The high rate of unfavorable outcomes has been attributed to poor patient selection rather than to the surgical procedure. [810] As people are always skeptical and prudent regarding health-related services, they will definitely not choose to have surgery if they find that PFD cannot bring them improvement. [11] Most studies of CMI decompression efficacy have considered symptoms, syringomyelia, CSF dynamics, or PCF volumetric changes, whereas few studies have attempted to predict surgical outcome based on preoperative PCF morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Chiari malformation type I (CM-I) is a well-known hindbrain disorder that is characterized by cerebellar tonsillar herniation behind the cervicomedullary junction, which is associated with the hypoplastic posterior cranial fossa, and often accompanied by syringomyelia. [ 1 2 5 ] Foramen magnum decompression (FMD) has been acknowledged as a standard surgical procedure for most of the symptomatic pediatric and adult patients with CM-I. [ 5 6 ] Incision of the dura mater at the posterior fossa is frequently required to relieve the symptoms; a Y-shaped dural incision is usually applied for effective decompression.…”
Section: Introductionmentioning
confidence: 99%